Woakes syndrome - Retno Sulistyo Wardani; Ika Dewi Mayangsari (Oto Rhino Laryngologica Indonesiana, 2014)
Background: Extensive nasal polyp growth in the paranasal sinuses can lead to bone erosion of the sinus walls and cause facial disfigurement due to continuous pressure or chronic inflammation. This extremely rare phenomenon is called Woakes syndrome. This syndrome consist of several symptoms include the destruction of ethmoid sinus that cause broadening of the bridge of the nose, frontal sinus aplasia and bronchiectasis. Purpose: To give complete information about the diagnosis and management of Woakes Syndrome. Case: A 16-year-old boy with deformity of the left nose, nasal obstruction and frequent episodes of rhinorrhea since 4 months before admission. Nasoendoscopic evaluation showedhuge nasal polyps filling the left nasal cavity, pushing the septum and narrowing the right nasal cavity. Histopathology result was edematous polyp with necrosis and massive bleeding without signs of malignancy. Management: Patient was managed in two stages operations. First, nasal polyp removal by FESS technique in general anesthesia, and the second stage four months later, was septorhinoplasty for aesthetic bridge reconstruction. Conclusion: Nasal polyps could be related to Woakes syndrome, characterized by broadening of nasal bridge which needs functional and aesthetic surgery. Keyword: Woakes Syndrome, nasal polyps, Functional Endoscopic Sinus Surgery, Septorhinoplasty ABSTRAKLatar Belakang: Polip hidung besar yang meluas dalam sinus paranasal dapat menyebabkan erosi dinding sinus dan menyebabkan cacat wajah akibat tekanan terus-menerus atau peradangan kronis. Fenomena ini sangat langka dan disebut sebagai sindrom Woakes. Sindrom ini terdiri dari beberapa gejala termasuk kerusakan dinding sinus etmoid yang menyebabkan hidung melebar, aplasia sinus frontal dan bronkiektasis. Tujuan: Untuk memberikan informasi yang lengkap tentang diagnosis dan penatalaksanaan Woakes Syndrome. Kasus: Seorang anak laki-laki 16 tahun dengan deformitas hidung kiri, hidung tersumbat dan pilek berulang sejak 4 bulan. Evaluasi nasoendokopi menunjukkanpolip hidung masif mengisi rongga hidung kiri, mendorong septum dan menyempitkan rongga hidung kanan. Pemeriksan histo-patologi memperlihatkan polip edematosa dengan nekrosis dan perdarahan masif tanpa tanda-tanda keganasan. Penatalaksanaan: Pada pasien dilakukan dua tahap tindakan. Pertama, dilakukan Bedah Sinus Endoskopik Fungsional (BSEF) dan polipektomi dalam anestesi umum, dan empat bulan kemudian pasien menjalani septorinoplasti untuk rekonstruksi wajah. Kesimpulan: Polip hidung pada kasus ini kemungkinan terkait dengan sindrom Woakes, ditandai dengan pelebaranpyramid hidung yang membutuhkan tindakan operasi fungsional dan estetika.Kata kunci: sindroma Woakes, polip hidung, Bedah Sinus Endoskopik Fungsional, Septorinoplasti.